Distribution, abundance, and clutch size of hawksbill turtle nests in Melaka, Malaysia - Mohd Salleh, Sarahaizad; Mohd Sah, Shahrul Anuar; Khan Chowdhury, Ahmed Jalal (Malaysian Society of Applied Biology, 2018)
The nesting of hawksbill turtle (Eretmochelys imbricata) was monitored from 2006 until 2014, while the eggs survival was monitored from 1990 until 2014 at the beaches of Melaka, Peninsular Malaysia. From 2006 until 2014, the yearly nesting ranged from 353 to 568 nests with a mean of 431.6 (n=9). Among the 21 recognized nesting beaches, five of the main beaches that included Padang Kemunting (55-107 nests), Pulau Upeh (36-111 nests), Kem Terendak (31-98 nests), Pasir Gembur (28-59 nests), and Tanjung Serai (14-60 nests) recorded the highest nesting in Melaka. Yearly number of live hatchlings ranged from 27.9% to 81.4% from 1990 until 2014. In 25 years, the overall number of live hatchlings produced was 491,643 hatchlings (53.4%) from 920,996 eggs. Hawksbill turtle eggs ranged from 9 to 212 eggs from the observation in 2013 and 2014, and most of the clutch sizes were deposited in a group of 121-150 eggs (36.2% observations). This study provides basic knowledge on the distribution and number of hawksbill turtle for a period of 25 years in Melaka; besides providing suggestion and recommendations to the conservation of this endangered species.